(untitled) (Research, Society and Development, 2021)
Some species of fungi are capable of causing mycotic infections. One of these infections is dermatophytosis, caused by a group of fungi, called dermatophytes, which comprises the genera Trichophyton, Microsporum and Epidermophyton. The treatment of the disease is carried out using conventional antifungals. The emergence of resistant strains has stimulated the development of natural medicines and the use of ozone gas. The objective of this research was to evaluate the antifungal activity of essential oils in natura and ozonized against the Trichophyton mentagrophytes ATTC 9533. Essential oils in natura and ozonated from Cinnamomum cassia, (L.) Presl), Eugenia caryphollata L. Merr. & L. M. Perry, Cymbopogon winterianus Jowitt, Eucalyptus globulus Labill, Eucalyptus staigeriana F. Muell. ex F. M. Bailey e Mentha piperita L. evaluated for antifungal activity. The oils were ozonized in corona equipment. The microdilution technique was used to assess the minimum inhibitory concentration (MIC) and the minimum fungicidal concentration (MFC). The fungicidal kinetics of essential oils were determined. C. winterianus C. cassia and E. caryphollata ozonated oils proved to be able to cancel Trichophyton mentagrophytes with exposure for 5-10 minutes, proving to be more efficient than those of eucalyptus and mint. In general, the results showed the antifungal activity of essential oils, pointing to the possibility of use in antifungal therapy against the dermatophyte evaluated. However, there is a need for studies on the safety in use and the effectiveness of essential oils.